'I did think it was a bit strange taking outdoor education online': exploration of initial teacher education students' online learning experiences in a tertiary outdoor education unit. Issue 1 (2nd January 2018) - Dyment, Janet; Downing, Jillian; Hill, Allen; Smith, Heidi
ABSTRACT: With a view to attracting more students and offering flexible learning opportunities, online teaching and learning is becoming increasingly wide-spread across the higher education sector. This research reports on the experiences of eight initial teacher education students who studied an outdoor education unit in the online space. Using a descriptive qualitative case study approach, the students were interviewed with a view to exploring their experiences of studying outdoor education in the online space. Students spoke about the ways in which the online teaching space, the role of the field experience and the assessment tasks contributed to, or detracted from, their learning experiences. Our study revealed that with careful design and delivery, the online space was an effective way to deliver a foundational outdoor education unit. This article concludes with a discussion of how these findings sit alongside recent papers that advance our understandings of teaching and learning in outdoor education.